2016
DOI: 10.11005/jbm.2016.23.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal Insufficiency Fracture after Ipsilateral Total Knee Arthroplasty

Abstract: Insufficiency fracture of the calcaneus is a rare entity. In the absence of trauma, evaluating a painful ankle in an elderly patient can be difficult and also it might be overlook the insufficiency fracture. We experienced a case of insufficiency calcaneus fracture that occurred after ipsilateral total knee arthroplasty. Here, we report our case with a review of literatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1,2 Furthermore, fragility fractures may occur in severe osteoporosis. 3-6 Even after ankle arthrodesis, a reduction in bone density in the calcaneus could persist for many years after fusion. 7,8 Studies on ankle and calcaneal fractures have shown that reduced bone density alters clinical outcomes after fracture fixation.…”
mentioning
confidence: 99%
“…1,2 Furthermore, fragility fractures may occur in severe osteoporosis. 3-6 Even after ankle arthrodesis, a reduction in bone density in the calcaneus could persist for many years after fusion. 7,8 Studies on ankle and calcaneal fractures have shown that reduced bone density alters clinical outcomes after fracture fixation.…”
mentioning
confidence: 99%